Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the equation [tex]\( 4^x - 2^x - 12 = 0 \)[/tex], let's go through the problem step by step.
First, we can rewrite [tex]\( 4^x \)[/tex] in terms of a common base with [tex]\( 2^x \)[/tex]. Notice that [tex]\( 4 = 2^2 \)[/tex], so we have:
[tex]\[ 4^x = (2^2)^x = (2^x)^2 \][/tex]
Substituting this back into the equation, we get:
[tex]\[ (2^x)^2 - 2^x - 12 = 0 \][/tex]
Let [tex]\( y = 2^x \)[/tex]. Our equation then becomes a quadratic equation in terms of [tex]\( y \)[/tex]:
[tex]\[ y^2 - y - 12 = 0 \][/tex]
Now, we can solve this quadratic equation using the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -12 \)[/tex].
Plugging in the values, we get:
[tex]\[ y = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-12)}}{2(1)} \][/tex]
[tex]\[ y = \frac{1 \pm \sqrt{1 + 48}}{2} \][/tex]
[tex]\[ y = \frac{1 \pm \sqrt{49}}{2} \][/tex]
[tex]\[ y = \frac{1 \pm 7}{2} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{1 + 7}{2} = \frac{8}{2} = 4 \][/tex]
[tex]\[ y = \frac{1 - 7}{2} = \frac{-6}{2} = -3 \][/tex]
Since [tex]\( y = 2^x \)[/tex], we now substitute back to find [tex]\( x \)[/tex]:
1. For [tex]\( y = 4 \)[/tex]:
[tex]\[ 2^x = 4 \][/tex]
[tex]\[ 2^x = 2^2 \][/tex]
[tex]\[ x = 2 \][/tex]
2. For [tex]\( y = -3 \)[/tex]:
[tex]\[ 2^x = -3 \][/tex]
Since [tex]\( 2^x \)[/tex] is always positive for real [tex]\( x \)[/tex], there are no real solutions for this case. Thus, we disregard this solution.
So, the only real solution from our initial transformation is [tex]\( x = 2 \)[/tex].
### Checking Against Provided Possible Answers
The provided possible answers are: [tex]\( x = -2 \)[/tex], [tex]\( x = 1 \)[/tex], [tex]\( x = 5 \)[/tex], and [tex]\( x = 2 \)[/tex].
Among these, only [tex]\( x = 2 \)[/tex] is a valid solution.
### The Solution
Therefore, the correct answer for [tex]\( 4^x - 2^x - 12 = 0 \)[/tex] is [tex]\( x = 2 \)[/tex].
First, we can rewrite [tex]\( 4^x \)[/tex] in terms of a common base with [tex]\( 2^x \)[/tex]. Notice that [tex]\( 4 = 2^2 \)[/tex], so we have:
[tex]\[ 4^x = (2^2)^x = (2^x)^2 \][/tex]
Substituting this back into the equation, we get:
[tex]\[ (2^x)^2 - 2^x - 12 = 0 \][/tex]
Let [tex]\( y = 2^x \)[/tex]. Our equation then becomes a quadratic equation in terms of [tex]\( y \)[/tex]:
[tex]\[ y^2 - y - 12 = 0 \][/tex]
Now, we can solve this quadratic equation using the quadratic formula:
[tex]\[ y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -12 \)[/tex].
Plugging in the values, we get:
[tex]\[ y = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-12)}}{2(1)} \][/tex]
[tex]\[ y = \frac{1 \pm \sqrt{1 + 48}}{2} \][/tex]
[tex]\[ y = \frac{1 \pm \sqrt{49}}{2} \][/tex]
[tex]\[ y = \frac{1 \pm 7}{2} \][/tex]
This gives us two solutions for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{1 + 7}{2} = \frac{8}{2} = 4 \][/tex]
[tex]\[ y = \frac{1 - 7}{2} = \frac{-6}{2} = -3 \][/tex]
Since [tex]\( y = 2^x \)[/tex], we now substitute back to find [tex]\( x \)[/tex]:
1. For [tex]\( y = 4 \)[/tex]:
[tex]\[ 2^x = 4 \][/tex]
[tex]\[ 2^x = 2^2 \][/tex]
[tex]\[ x = 2 \][/tex]
2. For [tex]\( y = -3 \)[/tex]:
[tex]\[ 2^x = -3 \][/tex]
Since [tex]\( 2^x \)[/tex] is always positive for real [tex]\( x \)[/tex], there are no real solutions for this case. Thus, we disregard this solution.
So, the only real solution from our initial transformation is [tex]\( x = 2 \)[/tex].
### Checking Against Provided Possible Answers
The provided possible answers are: [tex]\( x = -2 \)[/tex], [tex]\( x = 1 \)[/tex], [tex]\( x = 5 \)[/tex], and [tex]\( x = 2 \)[/tex].
Among these, only [tex]\( x = 2 \)[/tex] is a valid solution.
### The Solution
Therefore, the correct answer for [tex]\( 4^x - 2^x - 12 = 0 \)[/tex] is [tex]\( x = 2 \)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.